A study on the impact of flood towards student learning environment at UiTM Kota Bharu, Kelantan / Muhammad Arif Mohd Sidi, Nik Najmil Hafizin Ab Rahim and Wan Nur Anis Wan Din - Mohd Sidi, Muhammad Arif; Ab Rahim, Nik Najmil Hafizin; Wan Din, Wan Nur Anis (2017)
This research is about examining the impact of flood on 2014 towards learning environment. The subjects of interest about the learning environment are experience, facility, students' health and time management. To find out whether the flood on 2014 has effect on learning environment, this study examined some bachelor degree students of statistics in UiTM Kota Bharu, Kelantan that are experienced the flood on 2014 at UiTM Kota Bharu, Kelantan. This study use the questionnaires filled by the students to perform this analysis. Descriptive analysis is used to describe the characteristic of the respondents that experienced the flood on 2014, Pearson's Correlation coefficient to measures the strength and direction of a linear relationship between two variables that is dependent variable and independent variable, Independent t-test is used to test the mean difference between gender and learning environment, and finally used Multiple linear regression analysis is a statistical technique used to predict the response variable (Y) through several predictor variables (X's). At the end, we used the results of such tests and measurements to reach our conclusion. The conclusion in this study found that health, time management and experience are influence learning environment but facility does not influence student learning environment.